Green Technology Roadmapping: A Case Study In Fast Moving Consumer Good (FMCG) Companies In Indonesia - Laili, Nur (Journal of S&T Policy and R&D Management, 2014)
Degradation of environmental quality has become a global issue in the last decade. Industrial activity is one of the majorcauses of climate change and global warming. Governments in several countries have developed policies to reduce carbon emissions from industrial activity. The development and the use of innovative green technology products can be an alternative to reduce the impact of global warming due to carbon emissions from the industry. Adoption of green technology in the FMCG industry has become an interesting issue since it deals with the optimization of production costs and reduction of product prices that characterize the FMCG industry. This paper presents an overview of the adoption of green technology in the FMCG industry in Indonesia. A case study was conducted in one of the largest FMCG companies in Indonesia. The application of green technology is presented in the form of a technology roadmap for ten-year period between 2010 and 2020. The results showed that the adoption of green technology is the companys response to government policies and international regulations related to the environmental issues. The whole supply chain units of the company both internal and external, are involved in the adoption of green technology, while the technology itself comes from external source. The adoption of green technology has given some benefits to the company in the form of a decrease of environmental impacts caused by carbon emissions and hazardous waste. Another benefit is the adoption process increases the efficiency of production cost from economizing water and electricity uses. The indirect benefit from the adoption of green technology is the increasing company competitiveness through technological mastery and strong position of product in national FMCG market.